Rapid fractionation of mitochondria from mouse liver and heart reveals in vivo metabolite compartmentation. Issue 2 (27th October 2022) - Allen, Fay M.; Costa, Ana S. H.; Gruszczyk, Anja V.; Bates, Georgina R.; Prag, Hiran A.; Nikitopoulou, Efterpi; Viscomi, Carlo; Frezza, Christian; James, Andrew M.; Murphy, Michael P.
Abstract : The compartmentation and distribution of metabolites between mitochondria and the rest of the cell is a key parameter of cell signalling and pathology. Here, we have developed a rapid fractionation procedure that enables us to take mouse heart and liver from in vivo and within 30 s stabilise the distribution of metabolites between mitochondria and the cytosol by rapid cooling, homogenisation and dilution. This is followed by centrifugation of mitochondria through an oil layer to separate mitochondrial and cytosolic fractions for subsequent metabolic analysis. Using this procedure revealed the in vivo compartmentation of mitochondrial metabolites and will enable the assessment of the distribution of metabolites between the cytosol and mitochondria during a range of situations in vivo . Abstract : To assess the distribution of metabolites between mitochondria and the cytosol, we developed a rapid fractionation procedure. We take mouse heart/liver and within 30 s stabilise the distribution of metabolites by rapid cooling, homogenisation and dilution, followed by centrifugation of mitochondria through an oil layer to separate mitochondrial and cytosolic fractions for subsequent metabolic analysis.